2016
DOI: 10.1038/srep38294
|View full text |Cite
|
Sign up to set email alerts
|

Methylmercury induces the expression of TNF-α selectively in the brain of mice

Abstract: Methylmercury selectively damages the central nervous system (CNS). The tumor necrosis factor (TNF) superfamily includes representative cytokines that participate in the inflammatory response as well as cell survival, and apoptosis. In this study, we found that administration of methylmercury selectively induced TNF-α expression in the brain of mice. Although the accumulated mercury concentration in the liver and kidneys was greater than in the brain, TNF-α expression was induced to a greater extent in brain. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 45 publications
3
35
1
Order By: Relevance
“…Recent studies using mouse brain spheroid cultures have reported methylmercury-induced IL-6 in astrocytes to have a protective effect on the neurotoxicity caused by methylmercury [14]. However, our in vivo study using mice showed methylmercury induces the expression of tumor necrosis factor receptor (TNF)-α, IL-1β, and IL-19, but not IL-6, in the brain [15,16]. Therefore, the downstream factor that is induced by methylmercury via HOXB13 and is involved in methylmercury toxicity remains unknown.…”
Section: Introductioncontrasting
confidence: 61%
See 2 more Smart Citations
“…Recent studies using mouse brain spheroid cultures have reported methylmercury-induced IL-6 in astrocytes to have a protective effect on the neurotoxicity caused by methylmercury [14]. However, our in vivo study using mice showed methylmercury induces the expression of tumor necrosis factor receptor (TNF)-α, IL-1β, and IL-19, but not IL-6, in the brain [15,16]. Therefore, the downstream factor that is induced by methylmercury via HOXB13 and is involved in methylmercury toxicity remains unknown.…”
Section: Introductioncontrasting
confidence: 61%
“…The extracellularly released OSM is known to bind as a ligand to the OSM receptor (OSMR) or LIF receptor (LIFR) on the cell membrane [20,21]; however, knockdown of OSMR or/and LIFR did not affect methylmercury sensitivity ( Figure 5A,B). We have previously shown that addition of WP9QY, a peptide that mimics the ligand-binding site of the TNF receptor (TNFR), to the medium suppresses methylmercury toxicity [15]. Therefore, the effects of WP9QY on the enhancement of methylmercury toxicity via HOXB13 were examined.…”
Section: Tnf Receptor May Be Involved In the Enhancement Of Methylmermentioning
confidence: 99%
See 1 more Smart Citation
“…We previously performed expression variation analysis of gene clusters in the brain tissue of mice that were administered methylmercury, and identified chemokines (CCL3 and CCL4) , secretoglobin (SCGB3A1) and tumor necrosis factor α (TNFα) (Iwai-Shimada et al, 2016) as genes whose expression were increased specifically in the brain in response to methylmercury. This suggests that there is a transcription mechanism that is activated by methylmercury specifically in the brain.…”
Section: Introductionmentioning
confidence: 99%
“…Inorganic mercury present in the environment is a well established toxicant to human health. On absorption through the alimentary tract, mercury binds with the thio proteins, which plays an important role in the further metabolism of this metal [1][2][3][4][5][6] . Historically, plants have been used as folk medicine against various types of diseases.…”
Section: Introductionmentioning
confidence: 99%